Penggunaan Media Pembelajaran Quizizz untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Arrahim Arrahim; Hana Yulianti; Rini Endah Sugiharti (Universitas Negeri Padang, 2022)
This research is motivated by there are still children who have not reached the Minimum Completion Criteria. The low learning outcomes of students are due to lack of understanding when doing questions and lack of use of learning media. Therefore, quizizz learning media is used as a solution to overcome these problems, because quizizz learning media can make students more active in learning, Eliminates boredom in students, increases student motivation in learning so that it has an impact on optimal student learning outcomes. The research method used is Systematic Literature Review (SLR). By studying or studying and analyzing how the use of Quizizz Learning Media describes the Learning Outcomes of Elementary School Students. The analysis sample is 15 published scientific journals published in the range of 2020-2022. Those that have been excluded from several scientific articles use the keywords